Asking Practical Ethical Questions about Youth Participation - Knowles-Yánez, Kim (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2009)
This paper is based on case study research conducted in an economically depressed, immigrant gateway neighborhood of Escondido, California. This study has been in progress since 2005 and involves working with children at the local middle school on rights-based community environmental action research projects in coordination with student facilitators in an upper-division university class titled “Children and the Environment.” This case study has suggested inquiry into the practical ethical dimensions of working with children, administrators, and university students on action research. Examples of the ethical questions which arose during this study include: how can continuity for the middle school children be achieved as different groups of university students move in and out of the project as they take and finish the “Children and the Environment” class, and is it ethical for the middle school children’s work to be facilitated by university students only freshly trained in the action research technique? This paper explores these and other ethical questions involving power, coercion, tension over expectations, and obligation and provides direction for on-going ethical questions scholars should pursue in involving children in rights-based community environmental action research.